T'ai Chi as Exercise Among Middle-Aged and Elderly Chinese in Urban China - Birdee, Gurjeet S. (Mary Ann Liebert, Inc., 2013)
OBJECTIVES: T'ai chi is a form of mind–body practice used as exercise in China, though limited data are available on characteristics of t'ai chi users and factors associated with practice. METHODS: Characteristics of and factors associated with t'ai chi practice among middle-aged and elder Chinese in Shanghai China were analyzed utilizing baseline data from the Shanghai Women's Health Study and Shanghai Men's Health Study. Logistic regression modeling was used to identify independent factors associated with the practice of t'ai chi among men and women. RESULTS: T'ai chi is the most common form of regular exercise in Shanghai China among middle-aged and elderly persons (22%), including among women (28%) and men (15%). Other popular forms of exercise were walking (7%), dancing (4%), and jogging (3%). A majority of adults who practiced t'ai chi used it as their exclusive type of exercise (69%). Overall, t'ai chi practitioners as compared to nonpractitioners were more likely women, older, more educated, retired versus still working, and more likely to report chronic medical conditions including pulmonary, gastrointestinal, and cardiovascular conditions. T'ai chi activity was associated with other health behaviors including nonsmoking, consuming ginseng, and participating in other forms of physical exercise. CONCLUSIONS: T'ai chi is the predominant form of exercise among middle-aged and elderly Chinese in urban China, particularly among those with older age and chronic medical diseases. Future research is needed to see whether t'ai chi has similar or different benefits than conventional forms of exercise such as walking and jogging.